2018
DOI: 10.1016/j.hjc.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of left heart disease in COPD patients with pulmonary hypertension

Abstract: The use of echocardiographic criteria for the presence of PH is adequate for the screening of COPD patients. Patients with acute exacerbation of COPD and possible/likely PH demonstrate worse mortality compared to patients unlikely to have PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Notably, HFpEF has been discernible across all patients with confirmed pulmonary hypertension via right heart catheterization (RHC). These findings underscore the predominant role of left heart failure in precipitating pulmonary hypertension among patients with respiratory diseases and offer insights into the presence of severe pulmonary hypertension in some patients [60].…”
Section: Comorbidity and Pulmonary Arterial Hypertensionmentioning
confidence: 54%
“…Notably, HFpEF has been discernible across all patients with confirmed pulmonary hypertension via right heart catheterization (RHC). These findings underscore the predominant role of left heart failure in precipitating pulmonary hypertension among patients with respiratory diseases and offer insights into the presence of severe pulmonary hypertension in some patients [60].…”
Section: Comorbidity and Pulmonary Arterial Hypertensionmentioning
confidence: 54%
“…More importantly, it may help to detect other frequently associated cardiac pathologies, such as left ventricle and valve dysfunctions, which can cause group 2 PHT. For example, in their study, Lepida et al found that PHT was not only a consequence in patients with COPD, but it might also originate from the presence of left heart dysfunction (LHD) in up to 30% of the patients 18 . There are some studies investigating the value of the SX window in the evaluation of PHT and right heart function in COPD patients in outpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of cardiovascular disease is pulmonary arterial stiffness, which is increased in CLD compared with healthy controls [46] and particularly prominent in COPD, wherein it is also found in systemic arteries when patients develop PH [47]. Postcapillary PH (Group 2 PH, with normal PVR) is frequent in CLD (5–20% of ILD [48,49 ▪ ] and 12–62% of COPD [50–52] patients, depending on the population considered) and has great impact on morbidity and mortality [49 ▪ ,50,53]. Its prevalence may be underestimated, because the distinction between pre and postcapillary PH requires RHC, not indicated in most patients with CLD.…”
Section: Comorbidities and Effects Of The Underlying Lung Diseasementioning
confidence: 99%